Предмет: Алгебра,
автор: Tenignib
(2х-1)^4 - 26(2x - 1)^2 + 25 = 0 Help
alexeyderdun3003:
Розв'язати треба?
Ответы
Автор ответа:
0
Відповідь:
Пояснення:
На фото спрощення виразу
Приложения:
Автор ответа:
0
t^2-26t+25=0
t=1
t=25
(2x-1)^2=1
(2x-1)^2=25
x=0
x=1
x=-2
x=3
Ответ:x1=-2 x2=0 x3=1 x4=3
t=1
t=25
(2x-1)^2=1
(2x-1)^2=25
x=0
x=1
x=-2
x=3
Ответ:x1=-2 x2=0 x3=1 x4=3
Похожие вопросы
Предмет: Русский язык,
автор: elenafink
Предмет: Русский язык,
автор: nikita200408
Предмет: Русский язык,
автор: vadimxlupin9
Предмет: Математика,
автор: лджлдж
Предмет: Математика,
автор: rseraeva